2017
DOI: 10.1111/fwb.12957
|View full text |Cite
|
Sign up to set email alerts
|

Between‐lake variation in the trophic ecology of an invasive crayfish

Abstract: The trophic ecology of invasive species has important implications for their impacts on recipient ecosystems, with omnivorous invaders potentially affecting native species and processes over multiple trophic levels. The trophic ecology of invaders might be affected by both their body size and the characteristics of their habitat due to variation in energy requirements and resource availability. Here, using stable-isotope analysis, we investigated the trophic ecology of the invasive crayfish Procambarus clarkii… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 70 publications
(142 reference statements)
2
36
0
Order By: Relevance
“…There was, however, no significant difference in trophic position between littoral and pelagic individuals. Trophic positions of 3 indicated that P. clarkii feed on more than one trophic level and are thus omnivorous, as observed previously in the studied ecosystems (Jackson et al, ). This omnivorous diet was likely composed of a mixture of primary producers, invertebrates, and fish (eggs and larvae or carrion) in both habitats (Gutiérrez‐Yurrita et al, ).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…There was, however, no significant difference in trophic position between littoral and pelagic individuals. Trophic positions of 3 indicated that P. clarkii feed on more than one trophic level and are thus omnivorous, as observed previously in the studied ecosystems (Jackson et al, ). This omnivorous diet was likely composed of a mixture of primary producers, invertebrates, and fish (eggs and larvae or carrion) in both habitats (Gutiérrez‐Yurrita et al, ).…”
Section: Discussionsupporting
confidence: 81%
“…On the same day as crayfish sampling, putative trophic resources of P. clarkii were collected in three different locations in each habitat of each lake to capture potential spatial heterogeneity in their stable isotope values. Specifically, periphyton and leaf litter were collected from the littoral, as they represent important components of P. clarkii's diet (Alp et al, ; Jackson et al, ), while pelagic zooplankton was collected using a 200‐µm mesh net as we assume that pelagic individuals on muddy bottoms could consume detritus including zooplankton debris (Ruokonen, Kiljunen, Karjalainen, & Hämäläinen, ; Smart et al, ). Periphyton and zooplankton samples were freeze‐dried (−50°C for 5 days) and oven‐dried (60°C for 48 hr), respectively (further details available in Jackson et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, differences observed over time within an individual represent trait variation emerging from environmental variability or biological processes, such as phenology or sexual maturity (van de Pol & Wright, ). Between‐individual variability in traits has been found across a wide range of species, including arthropods (Jackson et al, ), amphibians (Araújo, Bolnick, Martinelli, Giaretta, & Reis, ), reptiles (Vander Zanden, Bjorndal, & Bolten, ), birds (Cherel, Quillfeldt, Delord, Weimerskirch, & Inger, ), mammals (Novak & Tinker, ) and fish (Litz et al, ). However, little is known on the respective contribution and temporal consistency of between‐ and within‐individual effects on the variability of trophic traits at the level of population and species (Novak & Tinker, ).…”
Section: Introductionmentioning
confidence: 99%